Kinerja Penyuluh Pertanian Lapangan (PPL) di Kabupaten Pesisir Selatan - Martadona, Ilham; Fauzi, Dian; Yeyendra, Windi (Jurnal KIRANA, 2024)
Agricultural instructor performance can be seen in the aspects of preparation, implementation, evaluation, and reporting, agricultural extension development and agricultural extension professional development. The performance of agricultural extension agents in general can be seen in the aspects of preparation, implementation, evaluation, and reporting, agricultural extension development and agricultural extension professional development. This study aims to find out (1) Describe the characteristics of field agricultural extension workers in Pesisir Selatan District; (2) Describe the extension activities in Pesisir Selatan Regency; (3) Analyze relationship between the characteristics of field agricultural extension, extension activities to the performance of field agricultural extension workers in Pesisir Selatan Regency. The analytical tools used are descriptive qualitative analysis, validity test, reliability test, Spearman rank correlation test. The results of this study indicate that agricultural extension workers in Pesisir Selatan District are dominated by males by 53.10 percent with a vulnerable age of 45-49 years, education level S1, average work experience 11-16 years, the number of assisted farmer groups is 12-16 farmer groups, and the working area is 80-111 kilometers. Preparation of agricultural extension is in very good category. Characteristics which include (age, education level, work experience, assisted farmer groups, work area) are significantly related to agricultural extension performance and extension activities which include (preparation, implementation, evaluation and reporting) are significantly related to agricultural extension performance variables Keywords: